DRIVING FORCES OF INTERNATIONAL LABOR MIGRATION: A STUDY ON INDONESIAN PROSPECTIVE MIGRANT WORKERS - Herdiana, Ike; Artaria, Myrtati Dyah; Alaydrus, Sayf Muhammad; Suen, Mein-Woei (Jurnal Biometrika dan Kependudukan, 2025)
International migration concerns the mobilization of individuals from one country to another. The intention of a certain group to participate in an international migration can be understood through various efforts, depending on the methods employed, frameworks used, populations observed, and variables considered. This study tried to identify various factors that influence the decision of prospective migrant workers to migrate out of Indonesia. This quantitative study used a survey method, with the approval of the Department of Manpower and Transmigration of East Java. This study involved 110 prospective migrant workers who filled out open-ended questionnaires. Descriptive analysis of the survey results was reported in the form of tabulations and percentages. The results show that demographic characteristics, such as sex, age, marital status, and destination, contribute to the decision to migrate abroad. Additionally, friends and family who were already working in the destination country were a significant influence. Conclusively, the push and pull factors have three themes, which are personal, social, and economic factors. Various combinations of these factors motivate prospective migrant workers to seek a better fate abroad. This research might help the government and non-governmental organizations to aid prospective migrant workers in managing their expectations and working to achieve their dreams through quality education and skills training for increased productivity.